Potential Force Algorithm with Kinematic Control as Path Planning for Disinfection Robot - Iswanto Suwarno; Wiwin A. Oktaviani; Yosi Apriani; Dhiya Uddin Rijalusalam; Anish Pandey (Universitas Muhammadiyah Yogyakarta, 2022)
The disinfection robot is a virus-sterilizing robot that uses a nonholonomic robot model. Route planning algorithms are needed to allow disinfection robots to sterilize rooms in unknown areas and perform the task while navigating using a potential field algorithm. There is a problem applying the algorithm to nonholonomic robots: avoiding obstacles. The proposed route planning algorithm has been transformed into a potential force used to plan the path of disinfection robots in static and dynamic environments and environments with static obstacles. A potential field algorithm is used. There are some issues when the potential force algorithm is applied to nonholonomic disinfection robots in the area. Like any other robot, it takes a long time to avoid static obstacles. Therefore, this paper proposed a potential force algorithm that allows a robot to move towards a target point while avoiding static obstacles. The algorithm showed that a modified potential field algorithm with potential force could be applied to differential-driven robots for path planning. The disinfection robot could avoid obstacles with a faster response using this algorithm.